2010
DOI: 10.1590/s1678-77572010000300003
|View full text |Cite
|
Sign up to set email alerts
|

Compliance improvement in periodontal maintenance

Abstract: ObjectivesThe aim of this study was to assess the influence of efforts applied to modify the patients' behavior towards periodontal maintenance.Material and MethodsPatients were classified into three groups: Complete Compliance (participation in all visits), Irregular Compliance (irregular participation, one or more missing appointments), and Noncompliance (abandoned or never returned to the program). Complete compliers received usual procedures of the maintenance visit. The irregular compliers and non-complie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
0
25
0
1
Order By: Relevance
“…Studies have shown that insufficient motivation may only result in short-term successes in periodontitis subjects [3,16]. In periodontics, there is now a tremendous onus on individually tailored periodontal treatment programs based on the patient behaviour patterns [17].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that insufficient motivation may only result in short-term successes in periodontitis subjects [3,16]. In periodontics, there is now a tremendous onus on individually tailored periodontal treatment programs based on the patient behaviour patterns [17].…”
Section: Discussionmentioning
confidence: 99%
“…Dental care is the maintenance of healthy teeth and gingiva 9 . Periodontal intervention programs, 10‐14 i.e., the methods to maintain healthy gingiva by periodontal treatment, including oral hygiene instruction, full‐mouth scaling and root planing (SRP), and periodontal flap surgery, also improved periodontal status.…”
mentioning
confidence: 99%
“…The results showed that carious enamel usually presents Zn-protoporphyrin and protoporphyrin IX. It is known that porphyrin fluorescence found in dental calculus and in carious dental hard tissue is closely linked to high bacterial activity [23]. Some bacteria rely on hemin iron-containing molecules as a source of iron, such as hemin or hemoglobin, and the inflammatory gingival condition may be a source of blood and an important source for porphyrin derivatives [24].…”
Section: Discussionmentioning
confidence: 99%